Wzloty, odchylenia i lamenty, czyli imitatorzy wobec potrzeby nowości - Buszewicz, Elwira (Śląskie Studia Polonistyczne, 2019)
Precursors and forerunners, when they seek for novelty, establish some norms and frameworks which, in turn, become defining for poetical genres and currents. So, what is the right of an imitator to search for new paths? The subject of the article are meta-poetic declarations of creators, who willingly and consciously follow in the footsteps of their great predecessors. The author points to the metaphors by means of which the poets defend their “space of freedoms” or concede to their powerlessness. The cases of the following poets are considered: Józef Bartłomiej Zimorowic in relation to Szymon Szymonowicz, Albert Ines and Andrzej Kanon in relation to Maciej Kazimierz Sarbiewski. Especially close attention was given to problematics and contexts of Albert Ines’s words prefacing a collection of poems that are quoted and translated in the article.